1998
DOI: 10.1097/00000539-199804000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Prostaglandin E1 for Treatment of Acute Lung Injury in Severe Multiple Organ Failure

Abstract: In patients with severe acute lung injury and multiple organ failure, inhaled prostaglandin E1 improved oxygenation and decreased venous admixture without affecting systemic hemodynamic variables. Controlled clinical trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…However, lack of sustained improvement in 30 -46% of infants and the need for specialized delivery systems make the treatment expensive and limit availability. Several investigators have explored the use of aerosolized prostaglandin E 1 (PGE 1 ) as a selective pulmonary vasodilator in patients with respiratory failure to improve oxygenation because of its selective action not only on the pulmonary circulation, but also on well-ventilated lung units (2)(3)(4)(5). We have previously described the safety and feasibility of inhaled PGE 1 (IPGE 1 ) in NHRF in a phase I/II unblinded clinical trial (5).…”
mentioning
confidence: 99%
“…However, lack of sustained improvement in 30 -46% of infants and the need for specialized delivery systems make the treatment expensive and limit availability. Several investigators have explored the use of aerosolized prostaglandin E 1 (PGE 1 ) as a selective pulmonary vasodilator in patients with respiratory failure to improve oxygenation because of its selective action not only on the pulmonary circulation, but also on well-ventilated lung units (2)(3)(4)(5). We have previously described the safety and feasibility of inhaled PGE 1 (IPGE 1 ) in NHRF in a phase I/II unblinded clinical trial (5).…”
mentioning
confidence: 99%
“…In an in vitro study, we have demonstrated that the emitted dose of IPGE 1 following jet nebulization in a neonatal ventilator circuit was 32-40% (26). In the present study, we used a high dose of IPGE 1 , 1200 ng/kg/min, corresponding to a total dose of ~3,500 μg of PGE 1 administered over 24 h. Compared to doses known to reduce pulmonary hypertension in patients (8-300 ng/kg/min), this represents a high dose (7)(8)(9)20,28,36). A dose of 1200 ng/ kg/min was chosen as this represents a dose four times the maximal dose that has been reported in humans and when given over a 24-hour period represents the cumulative dose that would be delivered over several days in the clinically used doses.…”
Section: Discussionmentioning
confidence: 88%
“…Intravenous PGE 1 (ivPGE 1 ) and PGI 2 , potent vasodilators used empirically in the treatment of NHRF, are associated with systemic hypotension and worsening of oxygenation due to increased venous admixture (2)(3)(4)(5)(6). This has led investigators to explore the delivery of PGE 1 and PGI 2 directly to the lungs as an inhalation, thus minimizing systemic effects and achieving selective pulmonary vasodilation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Compared to PGI 2 , PGE 1 has a shorter half-life, lower pH (6.3 versus 10.5), bronchodilator action, anti-proliferative and anti-inflammatory effects on the alveolar, interstitial and vascular spaces of the lung (8,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is lack of sustained improvement in 30 -46% of infants (1)(2)(3)(4); moreover, INO is a highly toxic molecule requiring expensive monitoring and scavenging systems for administration, making the treatment expensive and limiting availability. Aerosolized prostaglandins I 2 and E 1 have been reported to be effective selective pulmonary vasodilators in animals and human adults (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In addition, inhaled PGI 2 (IPGI 2 ) has also been reported to be effective in preterm and term newborns and children with pulmonary hypertension (20 -26).…”
mentioning
confidence: 99%